2017
DOI: 10.32612/uw.20804814.2017.2.pp.30-45
|View full text |Cite
|
Sign up to set email alerts
|

A Lexical Study of Comparisons with Typical Brand Users of Goods

Abstract: Niniejsza publikacja jest dostępną na licencji Creative Commons. Uznanie autorstwa-Użycie niekomercyjne-Bez utworów zależnych 3.0 Polska. Pewne prawa zastrzeżone na rzecz autora. Zezwala się na wykorzystanie publikacji zgodnie z licencją-pod warunkiem zachowania niniejszej informacji licencyjnej oraz wskazania autora jako właściciela praw do tekstu. Treść licencji jest dostępna na stronie:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…The image of the TBU reflects the qualities that are important from the consumer's point of view, while the acquisition of a brand refers to the qualities that a person wants to achieve (Gorbaniuk et al, 2021;Sirgy et al, 1997) or from which he/she wants to protect himself/herself (Bosnjak & Rudolph, 2008;Gorbaniuk et al, 2021), which ultimately translates into brand preference (Mangleburg et al, 1998). The image of a TBU may contain both positive and negative associations (Gorbaniuk et al, 2017(Gorbaniuk et al, , 2021 and is formed directly based on the consumer's own experiences and contacts with brand users or indirectly from other sources (Keller, 2003). User associations relate to many different dimensions, including personality dispositions and social aspects (Gorbaniuk et al, 2021), demographic characteristics (gender, age), psychographic factors (attitudes towards career or political institutions), and other factors (Gorbaniuk & Razmus, 2009).…”
Section: Brand Preference and Brand User Imagementioning
confidence: 99%
“…The image of the TBU reflects the qualities that are important from the consumer's point of view, while the acquisition of a brand refers to the qualities that a person wants to achieve (Gorbaniuk et al, 2021;Sirgy et al, 1997) or from which he/she wants to protect himself/herself (Bosnjak & Rudolph, 2008;Gorbaniuk et al, 2021), which ultimately translates into brand preference (Mangleburg et al, 1998). The image of a TBU may contain both positive and negative associations (Gorbaniuk et al, 2017(Gorbaniuk et al, , 2021 and is formed directly based on the consumer's own experiences and contacts with brand users or indirectly from other sources (Keller, 2003). User associations relate to many different dimensions, including personality dispositions and social aspects (Gorbaniuk et al, 2021), demographic characteristics (gender, age), psychographic factors (attitudes towards career or political institutions), and other factors (Gorbaniuk & Razmus, 2009).…”
Section: Brand Preference and Brand User Imagementioning
confidence: 99%
“…Researchers referring to congruence theory for many years focused mostly on the positive value added by brands to a consumer's self-image (Aguirre-Rodriguez et al, 2012), ignoring the aspect of negative traits associated with the brand, which were accentuated by few researchers (Bosnjak, 2010;Bosnjak & Rudolph, 2008). Relatively more recent studies (Gorbaniuk et al, 2017), have shown that negative traits account for nearly 30% of the typical user's image associations. This means that research on congruence themes may have ignored the important domain of congruence between consumer image and TBU.…”
Section: A Symbolic Brand Value and Self-tbu Congruencementioning
confidence: 99%
“…The direct measurement of congruence (Sirgy et al, 1997), consisted of three items for measuring the congruence of the user's self-image with the desired selfimage (α = .93), actual self-image (α = .93), and undesired self-image (α = .96), which was included due to the value of negative traits for congruence (Bosnjak & Rudolph, 2008) and the existence of negative associations with TBU (Gorbaniuk et al, 2017). The scales are presented in Appendix B.…”
Section: Operationalisationmentioning
confidence: 99%
“…The psycholexical research methodology has recently been employed to develop structural models of the image of marketing objects in lexical studies of, among others: brand image structure (Gorbaniuk 2011); brand user image (Gorbaniuk et al 2012;Gorbaniuk/Dudek 2016;Gorbaniuk/Kolańska/Wilczewski et al 2017); company image (Gorbaniuk/Razmus/Firlej et al 2017); political party image (Gorbaniuk/Kusak/ Kogut et al 2015); politicians (Gorbaniuk/Razmus/Slobodianyk et al 2017) and countries (Gorbaniuk/Omiotek 2011).…”
Section: Development Of Structural Models Based On Lexical Structuresmentioning
confidence: 99%